Intermediality as an Extension of The Postdramatic: Dramaturgical Trajectories in Pilihan Pembayun and Dialog Antigone - Yudiaryani Yudiaryani; Hirwan Kuardhani; Silvia Anggreni Purba; Wahid Nurcahyono; Pius Rino Pungkiawan; Antonius Janu Haryono; Fitria Rahmah (Journal of Urban Society's Arts, 2026)
This article examines how intermedial theatre operates as an extension of postdramatic conditions through contemporary Indonesian performance practices. Focusing on two practice-based works, Pilihan Pembayun and Dialog Antigone, the study analyses how dramaturgical configurations shift from body–tradition relations toward increasingly intermedial body–media formations. Rather than positioning intermediality as a separate aesthetic category, the article argues that intermedial theatre develops from the relational logic of postdramatic performance, in which meaning emerges through interactions among bodies, media, sound, space, and technological systems. Using a practice-as-research framework, the study examines dramaturgical structures, directing strategies, and intermedial compositions to explore how theatrical agency is redistributed across human and nonhuman elements. In Pilihan Pembayun, performative relations remain strongly connected to ritual memory, collective affect, and embodied tradition, while Dialog Antigone intensifies fragmentation through digital media, visual projections, and dispersed performative agencies. Through this comparative dramaturgical trajectory, the article demonstrates that intermediality transforms not only theatrical form but also the relational operation of power, embodiment, and spectatorship in contemporary performance. Furthermore, the article positions Indonesian theatre practice not merely as a local application of Western theory, but as a site of conceptual production contributing to global debates on postdramatic theatre, intermedial dramaturgy, and performance epistemology.